Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What can be the smallest value of $(a+b)$ , $a>0$ and $b>0$ where $(a+13b)$ is divisible by $11$ and $(a+11b)$ is divisible by $13$

This is what I have done so far.

We have

1) $a+ 13b = 11m$
2) $a + 11b = 13n$

$b = \dfrac{11m - 13n}{2}$ , $a = \dfrac{169n - 121m}{2}$

Since $a,b > 0$, we have that

$11m - 13n > 0$ and $169n - 121m > 0$
$\implies 11\cdot13m - 13^2n > 0$ and $13^2n - 11^2m > 0$
$\implies 11\cdot13m > 13^2n > 11^2m$ $\implies (\frac{11}{13}) m > n > (\frac{11}{13})^2m$

How to proceed from here?

share|improve this question
    
@John0417 The questions says that $a>0$ and $b>0$. –  Fly by Night Oct 31 '12 at 19:59
add comment

2 Answers 2

Equivalently $11 \vert (a+2b)$ and $13 \vert (a-2b)$.

Hence, $a+2b = 11m$ and $a-2b = 13n$.

This gives us that $$a = \dfrac{11m+13n}{2} = 6(m+n) + \dfrac{n-m}{2}$$ $$b = \dfrac{11m-13n}{4} = 3(m-n) - \dfrac{m+n}4 $$ This means $2 \vert (n-m)$ and $4 \vert (m+n)$. Hence, $m+n = 4 k_1$ and $n-m = 2k_2$. Hence, $$a = 24k_1 + k_2 > 0$$ and $$b = -6k_2-k_1 > 0$$ Hence, $k_2 > -24 k_1$ and $k_2< - \dfrac{k_1}6$.

$a+b = 23k_1 - 5k_2 \in \left(23 \dfrac56 k_1,143k_1\right)$.

Hence, for $a+b$ to be minimum, our first choice would be $k_1 = 1$.

If $k_1 = 1$, then $-24 < k_2 < -\dfrac16$.

Since $a+b$ goes as $-5k_2$, we want $k_2$ to take a small negative value i.e. $k_2$ should be close to zero and negative. Hence, $k_2 = -1$.

This gives that $$a=23, b=5 \text{ and }a+b = 28$$

share|improve this answer
add comment

$\rm\begin{eqnarray}{\bf Hint}\rm\quad a+13b &=&\rm 11m &\:\Rightarrow\:&\rm 13a+169b &=&\rm 143m\\ \rm a+11b &=&\rm 13n &\:\Rightarrow\:&\rm 11a+121b &=&\rm 143n\\ && &\:\Rightarrow\:&\rm\ \ 2a+\ \ 48b &=&\rm 143(m-n)\ \ \ by\ subtracting\ prior\ from\ first \end{eqnarray}$

Thus $\rm\:a + 24b = 143c.\:$ Its solution with minimal $\rm\:a+b\:$ is $\rm\:(a,b) = (23,5),\:$ since all other solutions arise by adding to $\rm\:(a,b)\:$ nonnegative multiples of $\rm\:(-1,6)\:$ or $\rm\:(24,-1),\:$ increasing $\rm\:a+b,$ viz.

$$\begin{eqnarray}\rm a+24b = 143&\:\Rightarrow\:&\rm (a,b) = (23,\ \ 5),\ (47,\ \ 4),\ (71,\ \ 3),\ \ldots\\ \rm a+24b = 286&\:\Rightarrow\:&\rm (a,b) = (22,11),\ (46,10),\ (70,\ \ 9),\ \ldots\\ \rm a+24b = 429&\:\Rightarrow\:&\rm (a,b) = (21,17),\ (45,16),\ (69,15),\ \ldots\\ \cdots && \cdots \end{eqnarray}$$ In this solution table, adding $\rm\:(24,-1)\:$ moves right, and adding $\rm\:(-1,6)\:$ moves down. But moving left or above the border by subtracting these terms results in a solution with $\rm\:a\:$ or $\rm\:b\:$ negative.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.